Microglial Dysregulation and Suicidality: A Stress-Diathesis Perspective - Baharikhoob, Paria; Kolla, Nathan J. (Frontiers in Psychiatry, 2020)
According to the stress-diathesis model of suicidal behavior, completed suicide depends on the interaction between psychosocial stressors and a trait-like susceptibility. While there are likely multiple biological processes at play in suicidal behavior, recent findings point to over-activation of microglia, the resident macrophages of the central nervous system, as implicated in stress-induced suicidal behavior. However, it remains unclear how microglial dysregulation can be integrated into a clinical model of suicidal behavior. Therefore, this narrative review aims to (1) examine the findings from human post-mortem and neuroimaging studies that report a relationship between microglial activation and suicidal behavior, and (2) update the clinical model of suicidal behavior to integrate the role of microglia. A systematic search of SCOPUS, PubMed, PsycINFO, and Embase databases revealed evidence of morphological alterations in microglia and increased translocator protein density in the brains of individuals with suicidality, pointing to a positive relationship between microglial dysregulation and suicidal behavior. The studies also suggested several pathological mechanisms leading to suicidal behavior that may involve microglial dysregulation, namely (1) enhanced metabolism of tryptophan to quinolinic acid through the kynurenine pathway and associated serotonin depletion; (2) increased quinolinic acid leading to excessive N-methyl-D-aspartate-signaling, resulting in potential disruption of the blood brain barrier; (3) increased quinolinic acid resulting in higher neurotoxicity, and; (4) elevated interleukin 6 contributing to loss of inhibition of glutamatergic neurons, causing heightened glutamate release and excitotoxicity. Based on these pathways, we reconceptualized the stress-diathesis theory of suicidal behavior to incorporate the role of microglial activity.